2020
DOI: 10.7748/ns.2020.e11562
|View full text |Cite
|
Sign up to set email alerts
|

Understanding equality and diversity in nursing practice

Abstract: Equality and diversity is a term heard frequently within nursing, healthcare and the wider workplace. The concept links to the UK NMC Code and will be relevant to other regulatory Codes worldwide. This focuses on the core value of treating patients and service users as individuals and with respect and dignity. This article explores equality and diversity, the current UK legal framework behind the concept and offers specific examples of where this may be breached and how nurses can reflect and enhance their pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Whilst having a voice can take the form of direct discussion, surveys such as those being analysed here can be understood as a means of enabling staff to have a voice within the organisation. The notion of voice within organisations is nevertheless complex as it is bound up in the complexity of organisational hierarchies and power structures which permeate organisations from the wider social structures of society placing members of social groups in relation to one another [ 28 ]. Thus, not everyone has equal access to use their voice or be heard.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst having a voice can take the form of direct discussion, surveys such as those being analysed here can be understood as a means of enabling staff to have a voice within the organisation. The notion of voice within organisations is nevertheless complex as it is bound up in the complexity of organisational hierarchies and power structures which permeate organisations from the wider social structures of society placing members of social groups in relation to one another [ 28 ]. Thus, not everyone has equal access to use their voice or be heard.…”
Section: Discussionmentioning
confidence: 99%
“…4). Colonisation is the backdrop for this wider context that has resulted in historic and current marginalisation and discrimination against tāngata whenua (Hobbs et al, 2019;Stenhouse, 2021). Failure to honour te Tiriti through equal partnership has deeply impacted otherwise wellfunctioning whānau, iwi and hapū social and wellbeing systems (Came et al, 2018).…”
Section: Te Tiriti O Waitangimentioning
confidence: 99%
“…Of these, three offered a strong critique of the "white" nature of the term diversity, in which they stated their understandings were embedded. It is suggested that exploration of white privilege, relational space and intersectionality would deepen critique of practitioner engagement with diversity and Māori (Boulton & Cvitanovic, 2021;Hobbs et al, 2019;Stenhouse, 2021).…”
Section: Education and The Fundamentals Of Social Workmentioning
confidence: 99%
“…This research specifically focuses on ethnicity as ethnic disparities have been shown to exist in the management of those with chronic pain (Ezenwa & Fleming, 2012; Kennel et al., 2019; Morales & Yong, 2021). Treating people as individuals, avoiding making assumptions, recognising diversity and individual decision‐making and respecting, and upholding peoples' dignity are not only key values of equality and diversity (Stenhouse, 2021), but also important in supporting self‐management of their chronic pain.…”
Section: Introductionmentioning
confidence: 99%